Islamic Religious Education in Building Insight Multicultural - Sarbaini, Sarbaini; Kustati, Martin; Sepriyanti, Nana (Journal International Inspire Education Technology, 2024)
Islamic religious education (PAI) taught in madrasas and public schools is felt has not been one hundred percent successful in making students be tolerant and open towards other communities outside himself. This type of research is a systematic literature review which is carried out by collecting and accumulating research related to community-based total sanitation evaluation. The keywords used for literature searches; "Islamic Education" and "Islamic Education in Multicultural Society". The literature sources used in the research come from online databases, namely Google Scholar and Garuda. the results of this research Multicultural Education is a development process that seeks to improve something that has existed from the beginning or previously existed, developing all human potential, education that respects plurality and heterogeneity, and education that respects and upholds cultural, ethnic, tribal and religious diversity. Multicultural religious learning can instill Islamic values multicultural to participants. So anti-multicultural values such as discrimination and violence can be avoided. Therefore, the learning process of Religious Education Multicultural Islam is recommended to be implemented because it can make things easier achieve the goals of Islamic religious education in forming knowledge, attitudes and students' skills in a unified and balanced manner